2008
DOI: 10.1037/0096-1523.34.5.1212
|View full text |Cite
|
Sign up to set email alerts
|

How to stop and change a response: The role of goal activation in multitasking.

Abstract: Multitasking was studied in the stop-change paradigm, in which the response for a primary GO1 task had to be stopped and replaced by a response for a secondary GO2 task on some trials. In 2 experiments, the delay between the stop signal and the change signal was manipulated to determine which task goals (GO1, GO2, or STOP) were involved in performance and to determine whether the goals were activated in series or in parallel. As the delay increased, the probability of responding on stop trials changed very lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
204
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(213 citation statements)
references
References 64 publications
8
204
1
Order By: Relevance
“…The strong similarities between the change-signal and withhold-signal trials are consistent with the idea that a stop process or goal is needed to quickly change a response (Verbruggen et al, 2008;Camalier et al, 2007). Furthermore, the results are in line with recent theoretical accounts and fMRI findings (e.g., Band et al, 2003;Mars et al, 2007;Kenner et al, 2010;Boecker et al, 2011), suggesting the same inhibitory mechanisms are at play when subjects have to cancel or replace a response.…”
Section: Processing Stages Of Signal Trials In the Change And Withholsupporting
confidence: 79%
See 1 more Smart Citation
“…The strong similarities between the change-signal and withhold-signal trials are consistent with the idea that a stop process or goal is needed to quickly change a response (Verbruggen et al, 2008;Camalier et al, 2007). Furthermore, the results are in line with recent theoretical accounts and fMRI findings (e.g., Band et al, 2003;Mars et al, 2007;Kenner et al, 2010;Boecker et al, 2011), suggesting the same inhibitory mechanisms are at play when subjects have to cancel or replace a response.…”
Section: Processing Stages Of Signal Trials In the Change And Withholsupporting
confidence: 79%
“…For example, Verbruggen, Schneider and Logan (2008) introduced in a stop-change paradigm a delay between the stop signal and the go2 signal to examine whether the go1 response can be inhibited simply by activating the go2 response (go1ç go2) or whether it also requires a top-down inhibition process (go1ç stop + go2). The results of two experiments were consistent with models that included a stop process.…”
Section: Withholding Vs Replacing a Responsementioning
confidence: 99%
“…Stop and go processes do not seem to share capacity in this way (e.g., Logan, 1981;Logan & Burkell, 1986;Verbruggen, Schneider, & Logan, 2008). Yamaguchi, Logan, and Bissett (2012) measured SSRT in a dual-task experiment in which subjects had to stop one of two go tasks.…”
Section: General and Special Race Modelsmentioning
confidence: 99%
“…Such coordination requires the organization of individual actions into a hierarchical structure that can be flexibly interrupted and altered to achieve a goal whenever necessary. A number of previous studies have demonstrated that people apply different strategies when coordinating complex motor plans [1][2][3] in situations requiring a chaining of different actions to achieve a goal; however, the neuronal mechanisms underlying the strategy that links individual actions in multi-component behaviour have remained elusive.…”
mentioning
confidence: 99%
“…However, an alternative strategy in which different task goals are activated with some temporal overlap (that is, parallel processing) hampers the efficient unfolding of multi-component behaviour, possibly because different actions interfere with each other and overstrain response selection capacities [1][2][3][4] .…”
mentioning
confidence: 99%